PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN PAK PASCA PANDEMI - Hura, Ros nila (Sekolah Tinggi Teologi Imauel Pacet, 2024)
ABSTRACTChristian Religious Education (PAK) is one of the subjects that needs to be taught in various schools. When the pandemic began to hit Indonesia, learning in schools experienced rapid changes, so inevitably learning in schools had to be done online. This makes teachers and students throughout Indonesia face new challenges in carrying out distance learning. Therefore, the use of technology is an alternative solution to overcome this problem. However, we need to realize that in reality the use of this technology does not only have positive impacts but also negative impacts. This should open the eyes of every educator and work hard to overcome things that have a negative impact on the use of technology in learning. Therefore, in this scientific paper the author discusses